ANALYSIS OF PROVERBS FORMED ON THE BASIS OF A MEDICAL LEXEME IN ENGLISH AND UZBEK (World Bulletin of Social Sciences, 2023)
This paper examined English proverbs and sayings and their Uzbek equivalents and example of medicine, as well as the causes that cause translation problems